If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -16 = -41 + 8x Reorder the terms: -16 + 3x = -41 + 8x Solving -16 + 3x = -41 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -16 + 3x + -8x = -41 + 8x + -8x Combine like terms: 3x + -8x = -5x -16 + -5x = -41 + 8x + -8x Combine like terms: 8x + -8x = 0 -16 + -5x = -41 + 0 -16 + -5x = -41 Add '16' to each side of the equation. -16 + 16 + -5x = -41 + 16 Combine like terms: -16 + 16 = 0 0 + -5x = -41 + 16 -5x = -41 + 16 Combine like terms: -41 + 16 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| e+(-4)=7 | | 3x^3+10x^2-4x-35=0 | | x^2+3x^2+2x= | | 3n+2n=5 | | X+-4.2=-3 | | x^5-4x^4+x^3-7x+1=0 | | -91=p-6(-p+7) | | -17x-23x=12x-2 | | -17x-23x=12x-2 | | x^2-x-6%x^2-5x+6 | | f(x)=zx^2+12x+14 | | 2(u-8)-1=-5(-5u+4)-5u | | (-15)+e=12 | | 12x=121 | | 45-2x(15-2)= | | 3v-12=2 | | 3x^20=41 | | 8(3m+1)= | | 5(-x+10)=5x+10 | | x+37=7 | | 19=-3.1+j | | 3(12)=y | | -8n+4(1+5a)=-6n-14 | | x-z=15 | | 6z+1=.30 | | -6(6n+5)=38-2n | | 3u-9+2(2u+3)=-7(u+3) | | x^2+25x-444=0 | | 1.3z-0.7(z+13)=0.6(z+5) | | -6(6n+5)=38-2n | | x^2+25x-444=0 | | 2e^6x=5e^9x |